(untitled) (Sustainability in Debate, 2019)
In Brazil, droughts are widespread and recurrent in the semiarid region, mainly due to its water vulnerability. Approximately 28 million people live in the region, which concentrates the highest proportion of people living in poverty in Brazil. If drought occurs intensively and extensively in densely populated areas, it can result in disaster when local capacities are insufficient to avoid significant damage. The risks associated with drought are related to the natural hazard, local vulnerabilities, response capacity, and mitigation policies. This study presents the challenges for the consolidation of a drought risk warning system in Brazil and proposes an initial structure for assigning responsibilities among the national institutions involved in the theme in order to guide actions for the risk mitigation.